Discours sur le colonialisme ; suivi de Discours sur la négritude - Césaire, Aimé (2015)
Comme naguère Jean-Jacques Rousseau dénonçait le scandale d'une société fondée sur l'inégalité, avec la même clarté, et un bonheur d'écriture que seule peut inspirer la passion du juste, Aimé Césaire prend ses distance par rapport au monde occidental et le juge. Ce discours est un acte d'accusation et de libération. Sont assignés quelques ténors de la civilisation blanche et de son idéologie mystifiante, l'Humanisme formel et froid. En pleine lumière sont exposées d'horribles réalités : la barbarie du colonisateur et le malheur du colonisé, le fait même de la colonisation qui n'est qu'une machine exploiteuse d'hommes et déshumanisante, une machine à détruire des civilisations qui étaient belles, dignes et fraternelles. C'est la première fois qu'avec cette force est proclamée, face à l'Occident, la valeur des cultures nègres. Mais la violence de la pureté du cri sont à la mesure d'une grande exigence, ce texte chaud, à chaque instant, témoigne du souci des hommes, d'une authentique universalité humaine. Il s'inscrit dans la lignée de ces textes majeurs qui ne cessent de réveiller en chacun de nous la générosité de la lucidité révolutionnaires. Le Discours sur le colonialisme est suivi du Discours sur la Négritude, qu'Aimé Césaire a prononcé à l'Université Internationale de Floride (Miami), en 1987.
Keywords: 1-Cinéma; 1-Histoire de l'art; 1-Jeux vidéo; 1-TV; 2-Histoire/Historiographie critique; 2-Théories et épistémologie postcoloniales et décoloniales; 3-Afrique (corpus analysé); 3-Amérique du Nord (corpus analysé); 4-Amérique du Nord (lieu de production du savoir); 5-Auteur.rice PANDC; 5-Auteur.rice noir.e; _Nettoyé

El color de la razón: racismo epistemológico y razón imperial - Castro-Gómez, Santiago; Eze, Emmanuel Chukwudi; Henry, Paget (Ediciones del Signo, 2014)
Keywords: 1-Cinéma; 1-Histoire de l'art; 1-Jeux vidéo; 1-TV; 2-Histoire/Historiographie critique; 2-Théories et épistémologie postcoloniales et décoloniales; 3-Afrique (corpus analysé); 3-Amérique centrale (corpus analysé); 3-Amérique du Nord (corpus analysé); 3-Amérique du Sud (corpus analysé); 4-Afrique (lieu de production du savoir); 4-Amérique du Nord (lieu de production du savoir); 4-Amérique du Sud (lieu de production du savoir); 5-Auteur.rice PANDC; 5-Auteur.rice noir.e; _Nettoyé

An Aesthetic of Blackness: Strange and Oppositional - hooks, bell (Belonging: A Culture of Place, 2019)
There was no meaningful attempt to counter the black aesthetic with conceptual criteria for creating and evaluating art which would simultaneously acknowledge its ideological content even as it allowed for expansive notions of artistic freedom. To re-open the creative space that much of the black aesthetic movement closed down, it seems vital for those involved in contemporary black arts to engage in a revitalized discussion of aesthetics. In part, a radical aesthetic acknowledges that the people are constantly changing positions, locations, that their needs and concerns vary, that these diverse directions must correspond with shifts in critical thinking. Innovative African-American artists have rarely documented their process, their critical thinking on the subject of aesthetics. Certainly many of the revolutionary, visionary critical perspectives on music that were inherent to John Coltrane’s oppositional aesthetics and his cultural production will never be shared because they were not fully documented.
Keywords: 1-Histoire de l'art; 2-Théories et épistémologie postcoloniales et décoloniales; 3-Amérique du Nord (corpus analysé); 4-Amérique du Nord (lieu de production du savoir); 5-Auteur.rice PANDC; 5-Auteur.rice noir.e; _Nettoyé

African American Art and Artists - Lewis, Samella (University of California Press, 2003)
Samella Lewis has brought African American Art and Artists fully up to date in this revised and expanded edition. The book now looks at the works and lives of artists from the eighteenth century to the present, including new work in traditional media as well as in installation art, mixed media, and digital/computer art. Generously and handsomely illustrated, the book continues to reveal the rich legacy of work by African American artists.
Keywords: 1-Histoire de l'art; 2-Analyses formalistes; 2-Approches sociologiques; 2-Histoire/Historiographie critique; 2-Théories et épistémologie postcoloniales et décoloniales; 3-Amérique du Nord (corpus analysé); 4-Amérique du Nord (lieu de production du savoir); 5-Auteur.rice PANDC; 5-Auteur.rice noir.e; 5-Créateur.rice PANDC; 5-Créateur.rice noir.e; _Nettoyé

Ain't I a Woman Black Women and Feminism - hooks, bell (Routledge, 2015)
This landmark work of history and theory challenges every accepted notion about the nature of black women’s lives. Ain’t I A Woman examines the impact of sexism on black women during slavery, the historic devaluation of black womanhood, black male sexism, racism within the recent women’s movement, and black women’s involvement with feminism. hooks refutes the antifeminist claim that black women are not victims of sexist oppression nor in need of an autonomous women’s movement. She pushes feminist dialogue to new limits by claiming that all progressive struggles are significant only when they take place within a broadly defined feminist movement which takes as its starting point that race, class, and sex are immutable facts of human existence. bell hooks’ insight as a black woman and a feminist extends the scope of feminist theory and practice for us all, and marks the emergence of a revitalized feminism in the 1980s.
Keywords: 1-Cinéma; 1-Histoire de l'art; 1-Jeux vidéo; 1-TV; 2-Approches sociologiques; 2-Genre et sexualité; 2-Histoire/Historiographie critique; 2-Théories et épistémologie postcoloniales et décoloniales; 3-Amérique du Nord (corpus analysé); 4-Amérique du Nord (lieu de production du savoir); 5-Auteur.rice PANDC; 5-Auteur.rice noir.e; _Nettoyé

Black Looks: Race and Representation - hooks, bell (Routledge, 2015)
"In the critical essays collected in Black Looks, bell hooks interrogates old narratives and argues for alternative ways to look at blackness, black subjectivity, and whiteness. Her focus is on spectatorship--in particular, the way blackness and black people are experienced in literature, music, television, and especially film--and her aim is to create a radical intervention into the way we talk about race and representation. As she describes: 'The essays in Black Looks are meant to challenge and unsettle, to disrupt and subvert.' As students, scholars, activists, intellectuals, and any other readers who have engaged with the book since its original release in 1992 can attest, that's exactly what these pieces do"(Provided by publisher)
Keywords: 1-Cinéma; 1-Histoire de l'art; 1-Jeux vidéo; 1-TV; 2-Approches sociologiques; 2-Genre et sexualité; 2-Histoire/Historiographie critique; 2-Théories et épistémologie postcoloniales et décoloniales; 2-Étude des représentations; 3-Amérique du Nord (corpus analysé); 4-Amérique du Nord (lieu de production du savoir); 5-Auteur.rice PANDC; 5-Auteur.rice noir.e; _Nettoyé

L'Atlantique noir: modernité et double conscience - Gilroy, Paul (Éditions Amsterdam, 2010)
Qu'est-ce que l'identité noire ? Contre ceux qui en défendent une conception ethniciste ou nationaliste, ou qui cherchent avant tout à en préserver l'authenticité, Paul Gilroy montre comment cette identité complexe, nourrie d'une diversité irréductible, repose sur l'existence d'un espace transnational en constante transformation, qui n'est pas spécifiquement africain, américain, caribéen ou britannique, mais tout cela à la fois : l'Atlantique noir. L'objet de ce livre est de donner à voir l''existence de cet espace constitué dès le XVIIe siècle à travers l'histoire de la traite négrière, de retracer ce réseau serré de relations, d'échanges à multiples sens, d'idées, d'hommes et de productions culturelles. Au fil de pages peuplées par les figures les plus hétéroclites, de Spike Lee à Walter Benjamin en passant par les Jubilee Singers, Richard Wright, W. E. B. Du Bois, Jimi Hendrix, Wynton Marsalis et Hegel, l'espace et le temps singuliers de l'Atlantique noir prennent forme et consistance de façon saisissante. La musique, mode d'expression de prédilection d'une culture enracinée dans l'expérience des terreurs indicibles de l'esclavage, avec ses usages et ses allers-retours inattendus d'un bord à l'autre de l'Atlantique, joue ici un rôle de premier plan. Le retour sur l'esclavage et son caractère intrinsèquement moderne, opéré dans les oeuvres de nombreux écrivains noirs, ouvre par ailleurs à une relecture critique de la modernité, d'une portée universelle, au même titre que la critique des conceptions figées et réductrices de l'identité.
Keywords: 1-Cinéma; 1-Histoire de l'art; 1-Jeux vidéo; 1-TV; 2-Approches sociologiques; 2-Histoire/Historiographie critique; 3-Afrique (corpus analysé); 3-Amérique du Nord (corpus analysé); 3-Europe (corpus analysé); 4-Europe (lieu de production du savoir); 5-Auteur.rice PANDC; 5-Auteur.rice noir.e; 5-Identités diasporiques; _Nettoyé

Black Art: Ancestral Legacy : The African Impulse in African-American Art. - Dallas Museum of Art (Dallas Museum of Art, 1990)
For the first time, a major exhibition examines the impact of African culture on black artists, both trained and self-taught, in a stunning range of 157 works which are variously bold, witty, historical, and mysterious. 49 biographical outlines; 320 illustrations, 170 in full color.
Keywords: 1-Histoire de l'art; 2-Approches sociologiques; 2-Théories et épistémologie postcoloniales et décoloniales; 2-Étude de la réception; 3-Afrique (corpus analysé); 3-Amérique du Nord (corpus analysé); 4-Amérique du Nord (lieu de production du savoir); 5-Auteur.rice PANDC; 5-Auteur.rice noir.e; 5-Créateur.rice PANDC; 5-Créateur.rice noir.e; _Nettoyé

Decolonizing the Camera: Photography in Racial Time - Sealy, Mark Anthony (Durham University, 2015)
This thesis argues that photography is tainted with ingrained racist ideologies that have been present since its earliest inception in 1839. It considers the act of photographing the Other as a site of Western violence, myth, fantasy and disavowal. It examines archival images through the prism of race, representation and human rights with the aim of extracting new meanings that bring the Other into focus. This is done by reading the images both against the politics of the time in which they were made and as contemporary objects at work in the political and cultural present. The thesis makes the case that photography is burdened with ideological fault-lines concerning race and rights. The fault-lines have been forged by cultural and colonial violence resulting in Western scopic regimes that have dominated and fixed the Other within an inescapable set of Western epistemologies that have been used to serve and enhance imperial perspectives on race. I argue that these perspectives are still active within the Western mindset manifest as benign acts of photographic empathy that work to ultimately bolster Western hegemonies and economies. This thesis is based on 25 years of experience as a researcher and curator of international photography exhibitions, direct research into archives in different continental settings, the presentation of papers in a variety of national and international contexts, and interviews withphotographers, curators and academics. My hypothesis is that the history of photography can only be complete if the voice of the subaltern is made critically present within it, so allowing us to engage with important political racial memory work that can help us re-read the past and reconfigure different meanings concerning history, race, rights and human recognition in the present. I argue that photography requires decolonising work to be carried out on its history. I propose that if we do not recognise the historical and political conjunctures of racial politics at work within photography and the effects on those that have been culturally erased, made invisible or less than human by such images, then we remain hemmed within established orthodoxies of colonial thought concerning the racialised body, the subaltern and the politics of human recognition.
Keywords: 1-Histoire de l'art; 2-Approches sociologiques; 2-Recherche-création; 2-Théories et épistémologie postcoloniales et décoloniales; 3-Amérique du Nord (corpus analysé); 3-Europe (corpus analysé); 4-Europe (lieu de production du savoir); 5-Auteur.rice PANDC; 5-Auteur.rice noir.e; _Nettoyé